The contribution of female health to economic development - David E. Bloom; Michael Kuhn; Klaus Prettner (Universität Hohenheim, Fakultät Wirtschafts- und Sozialwissenschaften, 2016)
We analyze the economic consequences for less developed countries of investing in female health. We do this through developing and calibrating a novel micro-founded dynamic general equilibrium model in which parents trade off the number of children against investments in their education and in which we allow for health-related gender differences in productivity. We show that better female health speeds up the demographic transition and thereby the take-off toward sustained economic growth. By contrast, male health improvements delay the transition and take-off because ceteris paribus they raise fertility. Investing in female health is therefore a potent lever for promoting development.
urn:nbn:de:bsz:100-opus-12695
Keywords: O11; I15; I25; J13; J16; 330; economic development; educational transition; female health; fertility transition; quality-quantity trade-off